Hubungan Motivasi Kerja Terhadap Kinerja Guru SMK Negeri X Surabaya - Wiharja, Radityo Yuda; Satwika, Yohana Wuri (Character Jurnal Penelitian Psikologi, 2024)
Performance is a work result achieved by a person in carrying out the tasks assigned to him which is based on skill, experience, seriousness and time. Performance measurement is necessary for everyone to influence an organization or company to achieve success. SMK X Surabaya already has competent teachers. However, sometimes there is a decline in teacher performance due to decreased work motivation which sometimes changes according to the teacher's condition. The role of the Principal in motivating teachers has often been carried out and there are several teachers who have carried out their duties well. All teachers are quite capable of completing lesson materials and are responsible for their duties but their performance still needs to be improved to achieve school goal. The subjects in this research were 30 teachers at SMK X Surabaya. The data collection technique used was teacher performance and teacher work motivation instruments, and used saturated sampling of teachers including permanent employees to determine research subjects. The analysis technique used is a product moment correlation test using SPSS 20.00 for Windows software.